Long-Term Hypoxia Negatively Influences Ca2+ Signaling in Basilar Arterial Myocytes of Fetal and Adult Sheep - Reid, Casey; Romero, Monica; Chang, Stephanie B.; Osman, Noah; Puglisi, Jose L.; Wilson, Christopher G.; Blood, Arlin B.; Zhang, Lubo; Wilson, Sean M. (Frontiers in Physiology, 2022)
Cerebral arterial vasoreactivity is vital to the regulation of cerebral blood flow. Depolarization of arterial myocytes elicits whole-cell Ca2+ oscillations as well as subcellular Ca2+ sparks due to activation of ryanodine receptors on the sarcoplasmic reticulum. Previous evidence illustrates that contraction of cerebral arteries from sheep and underlying Ca2+ signaling pathways are modified by age and that long-term hypoxia (LTH) causes aberrations in Ca2+ signaling pathways and downstream effectors impacting vasoregulation. We hypothesize that age and LTH affect the influence of membrane depolarization on whole-cell intracellular Ca2+ oscillations and sub-cellular Ca2+ spark activity in cerebral arteries. To test this hypothesis, we examined Ca2+ oscillatory and spark activities using confocal fluorescence imaging techniques of Fluo-4 loaded basilar arterial myocytes of low- and high-altitude term fetal (~145 days of gestation) and adult sheep, where high-altitude pregnant and non-pregnant sheep were placed at 3,801 m for >100 days. Ca2+ oscillations and sparks were recorded using an in-situ preparation evaluated in the absence or presence of 30 mM K+ (30K) to depolarize myocytes. Myocytes from adult animals tended to have a lower basal rate of whole-cell Ca2+ oscillatory activity and 30K increased the activity within cells. LTH decreased the ability of myocytes to respond to depolarization independent of age. These observations illustrate that both altitude and age play a role in affecting whole-cell and localized Ca2+ signaling, which are important to arterial vasoreactivity and cerebral blood flow.